Pengaruh Kualitas Produk Dan Harga Produk Terhadap Kepuasan Konsumen Batik Tulis Jasmine Khas Grobogan - Mochamad Hangga Novian (Universitas Kristen Indonesia Toraja, 2024)
This study aims to analyze the effect of product quality and product price on consumer satisfaction of jasmine batik typical of Grobogan. In testing whether there is a relationship between Product Quality and Price Indicators on Customer Satisfaction, researchers use explanatory quantitative methodology. This study took a population based on data from the National Civil Service Agency (BKN), namely the number of civil servants in Grobogan Regency in 2023 was 11,545 people, consisting of 4,914 male employees and 6,886 female employees. The results showed that there was a positive and significant effect of product quality on customer satisfaction of Batik Tulis Jasmine through the results of correlation and product moment testing. Then, it was found that there was a positive and significant effect of product price on consumer satisfaction of Batik Tulis Jasmine through the results of correlation and product moment testing. Researchers also found that there is a positive and significant effect of product quality and product price on customer satisfaction of Batik Tulis Jasmine through the results of multiple correlation testing.